Prevalence of iron-deficiency anemia in pregnant women with various thalassemia genotypes: Thoughts on iron supplementation in pregnant women with thalassemia genes - Wang, Min; Zhang, Xiaozhuang; Zhao, Yanhong; Zhang, Yubin; Lin, Yan; Xiao, Meifang; Li, Ling (Frontiers in Nutrition, 2022)
Background There are limited studies on iron-deficiency anemia (IDA) in carriers of various thalassemia genotypes. However, for pregnant women (PW) with high iron demand, ignoring the phenomenon of carrying the thalassemia genes combined with IDA may lead to adverse pregnancy outcomes. Methods The hematological phenotype indexes of 15,051 PW who received a prenatal diagnosis of thalassemia in our hospital were analyzed, and the plasma ferritin (PF) of 714 anemic pregnant women (APW) was determined. Results The results showed that 87.43% of APW without thalassemia suffered from IDA. Among APW with various thalassemia genotypes, we found that 40.00∼77.78% of subjects with α-thalassemia silent genotypes [αCS (or QS)α/αα (40.00%), –α3.7(or4.2)/αα (57.65%), and αWSα/αα (77.78%)] and 18.18∼84.21% of subjects with α-thalassemia minor genotypes [αCS (or QS)α/–α3.7(or4.2) (18.18%), –α3.7(or4.2)/–α3.7(or4.2) (40.00%), αα/–SEA (44.55%), and αWSα/–α3.7(or4.2) (84.21%)] developed IDA, while in subjects with α-thalassemia intermedia genotypes, only αWSα/–SEA was associated with IDA, with an incidence of 16.67%. However, the incidence of IDA in APW with common β-thalassemia minor genotypes (βCD17(A>T)/β, βCD41/42 (–TTCT)/β, βCD71/72(+A)/β, βIVS–II–654(C>T)/β, and β–28(A>G)/β) was less than 10.85%. In addition, the APW with β-thalassemia minor had a higher PF level than the APW without thalassemia. Conclusion Our study is the first to reveal differences in the prevalence of IDA among PW with various thalassemia genotypes, indicating that the possibility of IDA should be fully considered when managing PW with α-thalassemia silent or minor genotypes in high-risk areas, and that iron supplementation should be monitored dynamically for PW with β-thalassemia minor genotypes.